Experimentally altered rainfall regimes and host root traits affect grassland arbuscular mycorrhizal fungal communities. Issue 8 (12th March 2018) - Deveautour, Coline; Donn, Suzanne; Power, Sally A.; Bennett, Alison E.; Powell, Jeff R.
Abstract: Future climate scenarios predict changes in rainfall regimes. These changes are expected to affect plants via effects on the expression of root traits associated with water and nutrient uptake. Associated microorganisms may also respond to these new precipitation regimes, either directly in response to changes in the soil environment or indirectly in response to altered root trait expression. We characterized arbuscular mycorrhizal (AM) fungal communities in an Australian grassland exposed to experimentally altered rainfall regimes. We used Illumina sequencing to assess the responses of AM fungal communities associated with four plant species sampled in different watering treatments and evaluated the extent to which shifts were associated with changes in root traits. We observed that altered rainfall regimes affected the composition but not the richness of the AM fungal communities, and we found distinctive communities in the increased rainfall treatment. We found no evidence of altered rainfall regime effects via changes in host physiology because none of the studied traits were affected by changes in rainfall. However, specific root length was observed to correlate with AM fungal richness, while concentrations of phosphorus and calcium in root tissue and the proportion of root length allocated to fine roots were correlated to community composition. Our study provides evidence that climate change and its effects on rainfall may influence AM fungal community assembly, as do plant traits related to plant nutrition and water uptake. We did not find evidence that host responses to altered rainfall drive AM fungal community assembly in this grassland ecosystem.